Effects of Language Immersion versus Classroom Exposure on Advanced French Learners: An ERP Study - Alexandra Claire Brito (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
University students often report making significant advances in their second language (L2) ability after immersion in a nonnative language through study abroad. The degree to which late L2 learners can become nativelike in terms of L2 performance and brain processing is unclear in second language acquisition research. The link between L2 proficiency and learning context has been characterized in previous research, yet the role of learning experience in attaining nativelike brain processing of L2 remains to be elucidated. This study contrasts learners with advanced French proficiency who have attained this level with no, little, or more immersion experience through study abroad. By using empirical neurolinguistic techniques, I investigate the impact of immersion versus classroom experience on second language processing. Participants were advanced learners of French who are separated into groups based on amount of immersion experience. Participants read sentences in French, which were either correct or contained a subject-verb agreement error. These errors were of two types: either silent (written but not pronounced) or phonologically realized (written and pronounced). Using electroencephalography (EEG), I monitored the brain’s electrical activity during the sentence-reading task. The subsequent event-related potentials (ERPs) provide insight into how French morpho-syntax is being processed in the brain. By comparing these ERP signatures among the three groups and to those of native speakers (as reported by Carrasco-Ortiz and Frenck-Mestre 2014), I examine and interpret any differences in L2 processing. The results of this experiment replicate the finding that phonologically realized errors elicit more robust ERP signatures as compared to silent errors. Further, I observed a difference in L2 processing among the three groups: participants with more immersion showed more native-like ERP signatures as compared to equally proficient participants without such experience.
Keywords: language; linguistics; neurolinguistics; French; L1; L2; SLA; ERP; EEG; Immersion